Medial Congenital Elbow Luxation in a Dog - Montgomery, R. D.; Milton, J. L.; Hudson, J. A.; Pernell, R. T.; Finn-Bodner, S.T. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Medial congenital elbow luxation was diagnosed bilaterally in an 8-week-old Pomeranian. All previous reports of congenital elbow luxation in the dog have been lateral. Treatment principles used with lateral congenital elbow luxation were successfully utilized. The ability of congenital elbow luxations to be medial further confuses the aetiology.
Keywords: Elbow luxation; congenital; dog